NURSING FACULTY’ TRAITS AS PERCEIVED BY 04 YEAR GENERIC NURSING STUDENTS: A FOCUS GROUP STUDY - Shahida Khan1, Shazia Sultan2, Rubina Praveen3, Muhammad Yousif Bhatti4, Ghulam Mustafa Rajput5, Pir Bux Jokhio6. (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2021)
Teaching is a professional activity and it is strengthened through experiences and efforts. One of observes and evaluators of the teaching techniques of their teachers are the students. Therefore, Student input is paramount, if a faculty wants to improve teaching abilities. This research is planned in this connection. OBJECTIVE: The goal of this research is ‘to ascertain nursing students’ views about the characteristics of a good nursing faculty.’ METHODS AND MATERIAL: Two focus group discussions were arranged to collect the data through a -04-item open-ended questionnaire from female nursing BSN (G) students of a public sector university in Sindh, Pakistan. Ethical approval for the study wasgranted from the Ethical Review Committee, Peoples University of Medical & Health Sciences for Women, Nawabshah, SBA. The sampling technique was purposive. The method for data analysis was qualitative content analysis. RESULTS: The four major themes were identified as traits of the nursing faculty. Master of the teaching process, respecting students, autonomy, good communicator, physical and psychological traits. CONCLUSION: A good nursing faculty avoids oppressive and inflexible environment. S/he respects students’ autonomy and creates a teaching and learning environment that is based on caring, trusting relationship. No student is threatened. Each student is given enough space to learn according to his/her learning needs. This is the best way to create an environment of empowerment and autonomous decision-making practice. The environment helps students to transfer their classroom learning into practice and become productive learners.